2006
DOI: 10.1074/jbc.m601720200
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Control of Cited2 by Transforming Growth Factor β

Abstract: Cited2 is a transcription factor without typical DNA binding domains. Cited2 interacts with cAMP-responsive element-binding protein-binding protein (CBP)/p300, TFAP2, Lhx2, and nuclear receptors, such as peroxisome proliferator-activated receptor and estrogen receptor to function as a transcriptional modulator. Overexpression of Cited2 in Rat1 cells leads to tumor formation in nude mice, suggesting that Cited2 is a transforming gene. Through microarray analysis, Cited2 was found to be down-regulated by transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 67 publications
4
24
0
Order By: Relevance
“…It is indicated that TGF-b-mediated CITED2 downregulation in MDA-MB-231 cells occurs post-transcriptionally. 9 Thus, TGF-b mediated downregulation of CITED2 is regulated through a MYCdependent transcriptional control and a MYC independent post-transcriptional mechanism (Supplementary Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that TGF-b-mediated CITED2 downregulation in MDA-MB-231 cells occurs post-transcriptionally. 9 Thus, TGF-b mediated downregulation of CITED2 is regulated through a MYCdependent transcriptional control and a MYC independent post-transcriptional mechanism (Supplementary Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…The CITED2 siRNA sequence has been described previously (9, 16). Stable cells were selected in the presence of 1 µg/ml puromycin (Sigma-Aldrich) for one week and utilized for subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…CITED2 is also regulated post-transcriptionally. For instance, CITED2 mRNA instability is mediated via the Smad pathway during TGF-b stimulation (Chou and Yang, 2006). In addition, CITED2 expression can be regulated post-translationally.…”
Section: Hif-1a Inactivation By Cited2 Dh Shin Et Almentioning
confidence: 99%